Magnitude of NNM and associated factors among Newborns delivered at the North Shewa zone Public Health Hospital, Central Ethiopia: A multi-level analysis - Goyomsa, Girma Garedew; Deriba, Birhanu Senbeta; Wadejo, Meseret Moroda; Debela, Sisay Abebe; Amhare, Abebe Feyissa (Frontiers in Public Health, 2022)
Background: Neonatal near miss is a condition where a newborn nearly died between 0-28 days and survived either by chance or because of the quality of care they received. It is considered a major public health problem that contributes to the global burden of disease in both developed and less developing countries. For every one death, many others develop a severe complication. Despite, this reality there is a gap in magnitude and predictors of neonatal near miss in Ethiopia where the previous study focuses on neonatal death investigation. Thus, this study aims to determine the magnitude of neonatal near miss, and it's determinant among neonate delivered in north shewa district, central Ethiopia, Methods: A Facility based cross-sectional study was conducted among 747 newly delivered babies by using systematic random sampling technique in the public hospital of north shewa zone from February to May 2021. Neonatal near misses were identified by using the World Health Organization labeling criteria. Collected data were coded, entered, and cleaned by using EPI data 4.4.6 and analyzed using SPSS version 26 for analysis. Descriptive statistics were used to compute summary statistics and proportions. Variables at a cut-off value of (0.20) on bivariate and (0.05) on multivariate logistic regression were used to identify predictors. Result: The Prevalence of neonatal near miss were 36.3 %(95% CI = 32.9 – 39.6) per 1000 live birth. Participant occupation [AOR: 0.55, CI: 0.33-0.90], number of ANC follows up [AOR: 2.08; CI: 1.33-3.23], Still birth history [AOR: 2.63; CI: 1.37-5.05], Abortion history [AOR: 1.93; CI: 1.15-3.24], Non-vertex presentation [AOR: 2.12; CI: 1.28-3.53], Premature rupture of membrane [AOR: 2.39; CI: 1.53-3.72], and Placenta abruption [AOR: 4.7; CI: 1.13-20.23] were found to have statistically significant association with outcome. Conclusion and Recommendation: One-third of the neonates faced serious neonatal health conditions. In view of this, addressing modifiable obstetric risk factors through providing skilled and quality care to mothers during pregnancy, as well as during and after childbirth was important for improving neonatal health. Additionally, strengthening antenatal care services through provision of appropriate information for the mother and counseling about the consequences of abortion were crucial.